Antimicrobial Activity and Cell Selectivity of Synthetic and Biosynthetic Cationic Polymers - Venkatesh, Mayandi (2017)
The mammalian and microbial cell selectivity of synthetic and biosynthetic cationic polymers has been investigated. Among the polymers with peptide backbones, polymers containing amino side chains display greater antimicrobial activity than those with guanidine side chains, whereas ethylenimines display superior activity over allylamines. The biosynthetic polymer ε-polylysine (εPL) is noncytotoxic to primary human dermal fibroblasts at concentrations of up to 2,000 μg/ml, suggesting that the presence of an isopeptide backbone has greater cell selectivity than the presence of α-peptide backbones. Both εPL and linear polyethylenimine (LPEI) exhibit bactericidal properties by depolarizing the cytoplasmic membrane and disrupt preformed biofilms. εPL displays broad-spectrum antimicrobial properties against antibiotic-resistant Gram-negative and Gram-positive strains and fungi. εPL elicits rapid bactericidal activity against both Gram-negative and Gram-positive bacteria, and its biocompatibility index is superior to those of cationic antiseptic agents and LPEI. εPL does not interfere with the wound closure of injured rabbit corneas. In a rabbit model of bacterial keratitis, the topical application of εPL (0.3%, wt/vol) decreases the bacterial burden and severity of infections caused by Pseudomonas aeruginosa and Staphylococcus aureus strains. In vivo imaging studies confirm that εPL-treated corneas appeared transparent and nonedematous compared to untreated infected corneas. Taken together, our results highlight the potential of εPL in resolving topical microbial infections.